Islam, Fundamentalists & Democracy: A Perspective from Indonesia - Herdi Sahrasad; Al Chaidar Al Chaidar (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2015)
As a religion, Islam provides values, ethics, norms and guidelines, but not a quick panacea, for Islam and democracy in Indonesia. So it is very important for Islamic scholars, leaders and Muslim intelligentsia to make their people be aware and conscious that the fundamentalism, radicalism and violence are the wrong answer at the wrong time to address the problems. Fundamentalism and radicalism with violent face are not the answer to tackle the poverty, social crisis, environmental crisis, global inequities and various multi-dimensional problems in recent years. Islam will be come in handy, useful and meaningful if it can make a real contribution as values, ethics, morals, ideas, thoughts, solutions and philosophy for the communities in addressing the real issues, so that Islam would be menaningful and useful in overcoming radicalism and fundamnetalism. Will Indonesian Islam be capable and credible in dealing with this challenge? It depends on its leader and ‘ulamā’s.